Principles and practice of modern chromatographic methods - Robards, K. (Kevin); Ryan, Danielle (Academic Press, 2021)
Principles and Practice of Modern Chromatographic Methods, Second Edition takes a comprehensive, unified approach in its presentation of chromatographic techniques. Like the first edition, the book provides a scientifically rigid, but easy-to-follow presentation of chromatography concepts that begins with the purpose and intent of chromatographic theory - the "what and why that are left out of other books attempting to cover these principles. This fully revised second edition brings the content up-to-date, covering recent developments in several new sections and an additional chapter on composite methods. New topics include sample profiling, sample preparation, sustainable green chemistry, 2D chromatography, miniaturization/nano-LC, HILIC, and more.